2017
DOI: 10.2174/1871530317666170912152351
|View full text |Cite
|
Sign up to set email alerts
|

Penile and Testicular Measurements in Male Neonates and Infants: Single Center Egyptian Study

Abstract: The age-related values of penile and testicular measurements must be known to be able to determine the abnormal sizes and to monitor treatment of underlying diseases. Our study is a step to achieve accurate reference values of penile and testicular measurements for Egyptian male newborns and infants. Therefore multicenter studies are recommended to establish Egyptian norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It has been reported that mean penile length in newborn infants varied from 23 mm to 36 mm in many races (10,11,15,23,24). In our study, mean penile length was 25.1 mm.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that mean penile length in newborn infants varied from 23 mm to 36 mm in many races (10,11,15,23,24). In our study, mean penile length was 25.1 mm.…”
Section: Discussionsupporting
confidence: 47%
“…a SPL was positively and significantly correlated with height and testosterone but not with weight, estradiol, and BMI in both groups. was positively linked to weight, height, and head circumference (15). These articles were performed on neonates and did not study hormonal levels.…”
Section: Discussionmentioning
confidence: 99%
“…In another study a reference value for normal SPL in 1000 full term Egyptian boys aged 1 day to 13 years was reported (18) . Other cross-sectional study on 1850 healthy Egyptian full term boys aged 0 -24 months, reported the penile length and circumference (19) . Also, a reference values for penile length in healthy term Egyptian newborn infants was reported by other studies (20,16) .…”
Section: Discussionmentioning
confidence: 99%